Uses and gratifications of photo sharing on Instagram. Issue 168 (December 2022) - Menon, Devadas
Highlights: This research empirically analysed (N=639) the motives for photo sharing on Instagram. Uses and Gratification Theory (UGT) was used as a theoretical lens. The research identified seven gratifications for photo sharing on Instagram The study reported that active users with disclosure and peer influence gratifications shared more photos online. Abstract: Instagram is one of the fastest-growing photo sharing social media platforms. Drawing from the uses and gratification theory (U&G theory), this study examines the gratifications in photo sharing on Instagram. Participants were 639 respondents from India aged between 15 to 62 years. This study identified seven gratifications: disclosure, peer influence, trend influence, self-promotion, diversion, habitual pastime, and social interaction. Hierarchical regression of the survey reported that active users with disclosure and peer influence gratification shared more photos online. This study also found that: Age is in positive correlation with peer influence and negative correlation with diversion; gender differences were identified among disclosure, peer influence, self-promotion, and social interaction gratifications.